A comparative study of young and advanced boxers in terms of injuries. - abd Al-Munaem, Firas (International Journal of Psychosocial Rehabilitation, 2020)
The physical accident is considered the most difficult period that the athlete may pass through because it can affect his course and life, so from the organic physical side, there might be deformities, injuries, and functional disability, which affect the psychological aspect. After the dangerous accident, the athlete especially is affected from the psychological aspect in different degrees, and this accident contributed to understanding the attacked athlete in the boxing sport. So we try to push this phenomenon to the farthest meaning under the shadow of the symptoms of the psychological shock. The boxing game is considered from the individual games that might be played by all the sections of society, and it is not vacated from aggressive and wounded reflections that appeared in the match on the round of playing. The plenty of physical accidents at the boxer represented the fact of this sport and the reflections on the psychological dimension with circumstances and results, especially when the accident happened and the difficulty in regaining the abilities, although on the medical care and the try to apply the theory after the accident to the state of the psychological attack caused by the physical accident.The target of the research was to know the psychological reflections of the young and advanced boxers in the province of Diyala, where the society of research was comprised of the province clubs for boxing (young and advanced groups) for the sport season (2018-2019). The number of players was 135, divided among 11 clubs. In accordance with that, the researchers chose a sample of boxers from clubs who were affected psychologically by the boxing fighting; the number of boxers was 51 and they were divided into young and advanced groups, and they represented 38.51% of the total number. The result showed that there was a behavior and feeling that appeared that might be expressed involuntarily because of the deep psychological affection from the change and the deformity of the shape of the injured player. The researchers recommend that there should be a necessity and need for a psychological specialist with boxing sport clubs with in-training units and official championships to train the boxers psychologically in addition to the physical training.